Sistem Upah Buruh Tani Jagung Desa Sidoharjo Kecamatan Jati Agung Kabupaten Lampung Selatan dalam Perspektif Ekonomi Islam - Meda Heryanti; Afif Arrosyid; Sri Rahayu Ningsih (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
This examination means to decide the Compensation Framework for Corn Ranchers in Sidoharjo Town, Jati Agung Area, South Lampung Rule from an Islamic Monetary Point of view. The strategy utilized in this examination is illustrative subjective through perception, interviews obtained from essential, auxiliary and documentation information. Information investigation strategies use information decrease, information show and information confirmation techniques. Information legitimacy testing utilizes source triangulation, specialized triangulation, and time triangulation. In light of the exploration results, it shows that rural circumstances in Sidoharjo Town are excellent on the grounds that there is even more manor land and rice fields contrasted with private land. Sidoharjo Town has a heat and humidity, this impacts local area establishing examples and soil ripeness. So it is truly reasonable to be handled into horticultural land as need might arise. The corn wage framework utilized by individuals of Sidoharjo Town is a day to day work wage framework and in some cases utilizes a piece rate framework which has turned into a propensity each reap season. The pay framework for corn ranch laborers is carried out by individuals of Sidoharjo Town. Some of them are not as per Islamic financial matters, including giving unbalanced compensation. Land/ranch proprietors ought to furnish compensation as per the work commitment given by laborers. For the wages given to corn ranch laborers to be fitting, this is as per the aggregate arrangement, specifically the joint understanding between the homestead laborers and the land proprietor.